Infrared variable stars in the compact elliptical galaxy M32. Issue 1 (5th April 2021) - Jones, O C; Nally, C; Sharp, M J; McDonald, I; Boyer, M L; Meixner, M; Kemper, F; Ferguson, A M N; Goldman, S R; Rich, R M
ABSTRACT: Variable stars in the compact elliptical galaxy M32 are identified, using three epochs of photometry from the Spitzer Space Telescope at 3.6 and 4.5  μ m, separated by 32 to 381 d. We present a high-fidelity catalogue of sources detected in multiple epochs at both 3.6 and 4.5  μ m, which we analysed for stellar variability using a joint probability error-weighted flux difference. Of these, 83 stars are identified as candidate large-amplitude, long-period variables, with 28 considered high-confidence variables. The majority of the variable stars are classified as asymptotic giant branch star candidates using colour-magnitude diagrams. We find no evidence supporting a younger, infrared-bright stellar population in our M32 field.